2015
DOI: 10.1002/term.2052
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative therapy for hippocampal degenerative diseases: lessons from preclinical studies

Abstract: Increase in life expectancy has put neurodegenerative diseases on the rise. Amongst these, degenerative diseases involving hippocampus like Alzheimer's disease (AD) and temporal lobe epilepsy (TLE) are ranked higher as it is vulnerable to excitotoxicity induced neuronal dysfunction and death resulting in cognitive impairment. Modern medicines have not succeeded in halting the progression of these diseases rendering them incurable and often fatal. Under such scenario, regenerative studies employing stem cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 159 publications
(171 reference statements)
0
5
0
Order By: Relevance
“…However, the inflammatory microenvironment present at the injury site is hostile to neuroblast survival, limiting the capacity of the brain for self-regeneration and repair (Galindo et al, 2011 ). In the case of neurodegeneration, the rate of cell loss exceeds that of generation of new neurons (Venugopal et al, 2017 ). With the balance of damage to regeneration unable to be met by the brain, obtaining neural cells from exogenous sources able to augment or direct repair is an important potential therapeutic tool (Neirinckx et al, 2013 ).…”
Section: Stem Cell Neurogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…However, the inflammatory microenvironment present at the injury site is hostile to neuroblast survival, limiting the capacity of the brain for self-regeneration and repair (Galindo et al, 2011 ). In the case of neurodegeneration, the rate of cell loss exceeds that of generation of new neurons (Venugopal et al, 2017 ). With the balance of damage to regeneration unable to be met by the brain, obtaining neural cells from exogenous sources able to augment or direct repair is an important potential therapeutic tool (Neirinckx et al, 2013 ).…”
Section: Stem Cell Neurogenesismentioning
confidence: 99%
“…This includes embryoid body (EB) formation in the presence of retinoic acid or conditioned media (Kurosawa, 2007 ); or through a monolayer culture system in the presence of FGF and notch ligands together with the bone morphogenetic protein (BMP) antagonist, noggin (Ying et al, 2003 ; Kunath et al, 2007 ). In a mouse temporal lobe epilepsy model, ESC-derived neural progenitor cells (NPCs) displayed enhanced survival and differentiation in the GCL when transplanted into the dentate gyrus (Venugopal et al, 2017 ). Interestingly, a study using an Alzheimer's disease mouse model has shown transplantation of undifferentiated ESCs led to extensive teratoma formation (Wang et al, 2006 ).…”
Section: Neural Cell Sources For Therapeutic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal cord injury (SCI) is considered to be one of the most challenging central nervous system injuries, the serious complications and high rates of paraplegia caused by SCIs have brought great burden to individuals, families, and society ( Venugopal et al, 2017 ). Once damaged or degenerated, nerve cells cannot be self-repaired, which results in the permanent loss of function.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, iPSCs can provide a reliable platform for the study of the molecular mechanisms of GE. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Studies using iPSC technology to investigate the molecular mechanisms of GE have included studies focusing on Rett syndrome, Dravet syndrome, Phelan-McDermid syndrome (PMDS), and fragile X syndrome (FxS). Classic GE syndromes include childhood absence epilepsy (CAE), juvenile absence epilepsy (JAE), juvenile myoclonic epilepsy (JME), and epilepsy with generalized tonic-clonic seizures alone (GTCS).…”
mentioning
confidence: 99%